Peran Workshop Kewirausahaan dalam Meningkatkan Pemahaman NIB, PIRT, dan Sertifikasi Halal UMKM Kelurahan Kayumalue Pajeko - Anis Musarofah; Dilva Amanda; Nilam Silfia Nensi; Safira Wahyunita; Anisah Anisah; Mufrih Mufrih; Mirani Juniar; Dedy Rizky Bidullah; Juwaeriyah Juwaeriyah; Rusdin Rusdin (ARDHI : Jurnal Pengabdian Dalam Negri, 2025)
cro, Small, and Medium Enterprises (MSMEs) play a strategic role in Indonesia's economy but often face challenges in meeting legal requirements such as Business Identification Numbers (NIB), Household Industry Food Production Permits (PIRT), and Halal Certification. This study aims to analyze the role of Thematic KKN (Community Service Program) students in the Industrial Cluster in enhancing MSME actors' understanding of these legal aspects through entrepreneurship workshops. A case study was conducted on MSMEs in Kayumalue Pajeko Village.The method used was a participatory approach through workshops integrating theory and practice. The results showed that the workshops effectively improved MSME actors' understanding of the procedures for obtaining NIB, PIRT, and Halal Certification. Additionally, the program facilitated MSMEs in initiating the process of managing legal documents independently.Thematic KKN students acted as facilitators, providing direct guidance and assisting in overcoming obstacles such as limited initial knowledge and lack of access to technology. However, challenges such as limited mentoring time and technical barriers were also encountered.In conclusion, the program had a positive impact on MSME development in Kayumalue Pajeko and provided practical experience for students. Recommendations for program development include the need for continuous mentoring, collaboration with the government, and additional training to ensure sustainable outcomes.